CRITERIA FOR THE SAFE PERFORMANCE OF VIDEOTHORACOSCOPY IN PATIENTS WITH CHEST WOUND - O. V. Voskresensky (Неотложная медицинская помощь)
RElEVANCE. Hypotension caused by intrapleural bleeding or wound of the heart is an indication for thoracotomy in chest wound. drainage of the pleural space is performed in normotensive patients in the absence of immediate threat to life and other indications for thoracotomy. Thoracoscopy allows diagnosing and fixingintrapleural damage in patientswhen thoracotomy is not indicated. The main condition for the procedure is stable hemodynamics.MATERIAl AND METHODS. Medical histories of 591 patients operated on between 2002 and 2012 with the use of traditional methods and videothoracoscopy have been studied. Four expert groups were formed (drainage of pleural space, atypical thoracotomy, videothoracoscopy and typical thoracotomy), consisting of 375 patients, to determine the value of shock index and the pace of intrapleural bleeding, enough for a safe thoracoscopy. We used binary logistic regression (ROc analysis), studying the findings.THE RESULTS. It was found that the safe performance of thoracoscopic surgery for a chest injury is reasonable when the value of shock index is less than 0.97 and the pace of intrapleural bleeding is less than 250 ml/hour.CONCLUSION. The retrospective study determined the safety parameters to perform thoracoscopyin patients with chest wound.